The phenotypic plasticity of developmental modules - Sharma, Aabha I. (EvoDevo, 2016)
BACKGROUND: Organisms develop and evolve in a modular fashion, but how individual modules interact with the environment remains poorly understood. Phenotypically plastic traits are often under selection, and studies are needed to address how traits respond to the environment in a modular fashion. In this study, tissue-specific plasticity of melanic spots was examined in the large milkweed bug, Oncopeltus fasciatus. RESULTS: Although the size of the abdominal melanic bands varied according to rearing temperatures, wing melanic bands were more robust. To explore the regulation of abdominal pigmentation plasticity, candidate genes involved in abdominal melanic spot patterning and biosynthesis of melanin were analyzed. While the knockdown of dopa decarboxylase (Ddc) led to lighter pigmentation in both the wings and the abdomen, the shape of the melanic elements remained unaffected. Although the knockdown of Abdominal-B (Abd-B) partially phenocopied the low-temperature phenotype, the abdominal bands were still sensitive to temperature shifts. These observations suggest that regulators downstream of Abd-B but upstream of DDC are responsible for the temperature response of the abdomen. Ablation of wings led to the regeneration of a smaller wing with reduced melanic bands that were shifted proximally. In addition, the knockdown of the Wnt signaling nuclear effector genes, armadillo1 and armadillo 2, altered both the melanic bands and the wing shape. Thus, the pleiotropic effects of Wnt signaling may constrain the amount of plasticity in wing melanic bands. CONCLUSIONS: We propose that when traits are regulated by distinct pre-patterning mechanisms, they can respond to the environment in a modular fashion, whereas when the environment impacts developmental regulators that are shared between different modules, phenotypic plasticity can manifest as a developmentally integrated system. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (doi:10.1186/s13227-016-0053-7) contains supplementary material, which is available to authorized users.